Hubungan Antara Gaya Kepemimpinan Kepala RuangDengan Motivasi Kerja Perawat PelaksanaDi Rumah Sakit Islam Surakarta - Zulfikhar, Muhammad Shoqibul Iza; , Supratman, SKM., M.Kep., Ph.D (2016)
Leadership is the ability to provide a constructive influence others to do the business of the cooperative achieve the planned objectives. Motivation is form of strength, force or power, or a state of readiness is complex and encouragement within the individual to move towards a certain goal. Motivation was a nurse may change due to factors that influence it. the objective was aim know correlation between leadership style of head room with work motivation of nurses. This research is a quantitative and research method used correlation approach. population are 232 nursing staff. sample are 56 nurse practitioner with taking sample was using simple random sampling technique. instrument research of leadership style and motivation nursing staff using questionnaire. data analysis using Chi Square test. the results obtained data. 5 respondents (8.9%) to implement autocratic leadership style, 49 respondents (87.5%) apply democratic leadership style, 2 respondents head room (3.6%) to implement free act leadership style. 4 respondents (63.2%) have medium motivation to work, 52 respondents (92.9%) had high motivation. Chi Square statistic test results with a significance of p = 0.024. the results concluded there was correlation between leadership style of head room with work motivation of nurses in Surakarta Islamic Hospital.